Beyond Wage Bill Ceilings : The Impact of Government Fiscal and Human Resource Management Policies on the Health Workforce in Developing Countries, Background Country Study for Rwanda - World Bank (Washington, DC, 2013)
One of the main explanations put forth on why access to health workers is so low in developing countries is that there are insufficient resources within the public sector to pay the wage bill - the salary and allowance payments - of an expanded health workforce. In turn, the lack of wage bill resources for the health sector is thought to be a direct result of restrictive macroeconomic policies that limit the expansion of the overall public sector wage bill. The overarching message in this report is that, despite the relative contraction of the public sector wage bill, Rwanda has not only protected the health sector, but has succeeded through decentralization and the introduction of performance-based financing in linking salaries to performance in the health sector. The decentralization of budgets, along with the implementation of the performance-based grants scheme, has had two major effects. First, it has increased the resource envelope available for hiring health workers since there is a lot of flexibility in how the performance based grants can be used. Second, it has linked payments to health workers with performance, since the salary top amounts paid out of the grants are linked to service delivery results.